Molecular genetic testing in athletes: Why and when a position statement from the Italian Society of Sports Cardiology. (1st October 2022) - Castelletti, Silvia; Zorzi, Alessandro; Ballardini, Enrico; Basso, Cristina; Biffi, Alessandro; Brancati, Francesco; Cavarretta, Elena; Crotti, Lia; Contursi, Maurizio; D'Aleo, Antonio; D'Ascenzi, Flavio; Delise, Pietro; et al.
Abstract: Molecular genetic testing is an increasingly available test to support the clinical diagnosis of inherited cardiovascular diseases through identification of pathogenic gene variants and to make a preclinical genetic diagnosis among proband's family members (so-called "cascade family screening"). In athletes, the added value of molecular genetic testing is to assist in discriminating between physiological adaptive changes of the athlete's heart and inherited cardiovascular diseases, in the presence of overlapping phenotypic features such as ECG changes, imaging abnormalities or arrhythmias ("grey zone"). Additional benefits of molecular genetic testing in the athlete include the potential impact on the disease risk stratification and the implications for eligibility to competitive sports. This position statement of the Italian Society of Sports Cardiology aims to guide general sports medical physicians and sports cardiologists on clinical decision as why and when to perform a molecular genetic testing in the athlete, highlighting strengths and weaknesses for each inherited cardiovascular disease at-risk of sudden cardiac death during sport. The importance of early (preclinical) diagnosis to prevent the negative effects of exercise on phenotypic expression, disease progression and worsening of the arrhythmogenic substrate is also addressed. Highlights: Molecular genetic test is an increasingly available test to support the clinical diagnosis of inherited cardiovascular diseases. In athletes, molecular genetic test may assist in discriminating between athlete's heart and inherited cardiovascular diseases. Additional benefits of molecular genetic testing in the athlete include the potential impact on risk stratification and sports recommendations. This position statement aims to guide on clinical decision as why and when to perform a molecular genetic test in the athlete.